Sculpting the brainstem: understanding brainstem anatomy using modelling clay / Muhammad Zaid Zainuddin ...[et al.] - Zainuddin, Muhammad Zaid; Husin, Andrean; Razlan, Aimi Nadia; Abdul Malik, Muhd Maaruf (Universiti Teknologi MARA Kelantan, 2020)
Preclinical science students lack the understanding of complex structures such as the central nervous system as they lack firm understanding of its basic anatomical structure. As brainstem anatomy is essential to the function of the central nervous system, a weak grasp of its basic structure stands as a barrier when students delve into more complex matters such as neurophysiology and neuropathology. The aim of this teaching and learning method is to ease and improve students understanding of the brainstem, its relations with surrounding structures as well as the anatomical origin of the cranial nerves. This method is unique as it incorporates sculpting and modelling into a modern learning environment as well as developing students fine motor skills alongside visualspatial cognitive abilities. This method allows creativity, imagination and fun into the learning environment without neglecting the main aim of understanding anatomical structures. Clay modelling and sculpting has tremendously impacted student understanding towards the focused structure as it lifts 2D images from textbooks into handmade 3D models. By studying 2D diagrams, and making 3D models, students have a better appreciation and understanding towards complex anatomical structures as they are required to study deep structures first before building towards superficial structures. After constructing the brainstem model, students find it easier to identify structures of the brainstem as well as its relation towards other structures. This method stands as a precursor towards better anatomy teaching and learning resources and will benefit anatomy students worldwide ranging from primary to tertiary education